Synthesis of MoS2/SrZrO3 heterostructures and their photocatalytic H2 evolution under UV irradiation. Issue 1 (1st December 2014) - Tian, Qingwen; Zhang, Li; Liu, Jiahui; Li, Naixu; Ma, Quanhong; Zhou, Jiancheng; Sun, Yueming
Abstract : A novel heterojunction of a MoS2 /SrZrO3 photocatalyst was successfully synthesized via a simple hydrothermal process and applied to photocatalytic H2 evolution under UV light irradiation. Abstract : A novel heterojunction of a MoS2 /SrZrO3 photocatalyst was successfully synthesized via a simple hydrothermal process and applied to photocatalytic H2 evolution under UV light irradiation. The samples were characterized by X-ray diffraction, UV-vis absorption spectroscopy, scanning and transmission electron microscopy, X-ray photoemission spectroscopy, energy dispersive X-ray spectroscopy and EDX mapping. The heterostructure with an optimal content of 0.05 wt% MoS2 exhibits the highest H2 evolution rate of 5.31 mmol h −1 . This is due to the junction between SrZrO3 and MoS2, which suppresses the recombination of photogenerated electrons and holes. Our work indicated that the prepared MoS2 /SrZrO3 heterostructured photocatalyst can be used as an effective material for water splitting.